2015
DOI: 10.1371/journal.pone.0127705
|View full text |Cite
|
Sign up to set email alerts
|

FTO Inhibits Insulin Secretion and Promotes NF-κB Activation through Positively Regulating ROS Production in Pancreatic β cells

Abstract: FTO (Fat mass and obesity-associated) is associated with increased risk of obesity and type 2 diabetes incurrence. Pancreas islet β cells dysfunction and insulin resistance are major causes of type 2 diabetes. However, whether FTO plays an important functional role in pancreatic β cells as well as the related molecular mechanism is still unclear. In the present study, the tissue expression profile of FTO was firstly determined using quantitative PCR and western blot. FTO is widely expressed in various tissues … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
14
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(16 citation statements)
references
References 36 publications
2
14
0
Order By: Relevance
“…Methylation level play a very important role in gene expression [33]. Two previous studies found that FTO expression level was associated with insulin secretion, which may lead T2DM [34,35].…”
Section: Discussionmentioning
confidence: 99%
“…Methylation level play a very important role in gene expression [33]. Two previous studies found that FTO expression level was associated with insulin secretion, which may lead T2DM [34,35].…”
Section: Discussionmentioning
confidence: 99%
“…In this work we decided to study whetherand how-age, metabolic status (normal birth weight vs. IUGR), and energy intake (low vs. high diet) directly influence FTO protein expression. The distribution of Fto mRNA and protein levels was previously studied by several research groups, primarily using rodent models 26,29,31,42,[47][48][49] . The role of Fto in rodents is, however, limited as compared to humans.…”
Section: Discussionmentioning
confidence: 99%
“…One of our main discovery was that FTO protein levels in the pancreas were associated with energy intake: low on low energy diet and high on high energy diet, compared to normal diet. Earlier in vitro studies showed that FTO overexpression in MIN6 (mouse insulinoma) cells significantly inhibited insulin secretion in the presence of glucose, but did not affect insulin expression 47 . As a result, we argue that increased FTO levels in the pancreas may directly influence insulin release from beta cells.…”
Section: Scientific Reports |mentioning
confidence: 99%
See 1 more Smart Citation
“…Several groups have investigated the functional role of FTO in pancreatic islets using different experimental models. Overexpression of FTO in rat INS-1 cells appeared to affect first wave insulin secretion (Russell and Morgan, 2011), whereas overexpression in mouse MIN6 cells resulted in the inhibition of GSIS without changes in insulin gene expression (Fan et al, 2015). Given the discrepant results of these studies, in addition to the caveats associated with overexpression studies, perhaps the more relevant functional assessment was the use of siRNA knockdown to deplete FTO in an engineered human insulin secretion reporter rat β cell line (GRINCH) (Taneera et al, 2018).…”
Section: M6a Rna Methylationmentioning
confidence: 99%